CORPORATE SOCIAL RESPONSIBILITY AND DEPOSIT MONEY BANKS’ PERFORMANCE: A STUDY OF GUARANTEE TRUST BANK NIGERIA, PLC (2006-2018) - Chukwuma Onwuagana, Okafor (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
From reviewed literature, many organizations used increase in total assets as the only way to enhance deposit money banks’ performance. This has made many firms commit so much on increasing its assets. However, there are other factors that enhance banks’ performance with this study arguing that corporate social responsibility can be one of such factors that enhances the performance of banks. The main objective of the study therefore was to examine the effect of corporate social responsibility on deposit money banks’ performance with special reference to Guarantee Trust Bank PLC in Nigeria (GT Bank). The study used secondary data for the period 2006 till 2018 and also used the multiple regression econometric analysis to analyze the data. The Augmented Dickey-Fuller unit root test indicated that all the variables were stationary at levels. The result of the multiple regression analysis showed that there was a positive and significant effect of corporate social responsibility on the performance of GT Bank. The study therefore recommended that all stakeholders and shareholders should ensure that they encourage the GT Bank to have serious commitment towards corporate social responsibility as this has added value to their investment in the long run and also maximize shareholders’ wealth.